Laboratory Interventions to Eliminate Unnecessary Rapid COVID-19 Testing During a Reagent Shortage. Issue 3 (1st June 2022) - Wulff, Regina T; Qiu, Yuqing; Wu, Caroline; Calfee, David P; Singh, Harjot K; Hatch, Ian; Steel, Peter A D; Scofi, Jean E; Westblade, Lars F; Cushing, Melissa M
Abstract: Objectives: In the fall of 2020, US medical centers were running out of rapid coronavirus disease 2019 (COVID-19) tests. The aim of this study is to evaluate the impact of an intervention to eliminate rapid test misutilization and to quantify the effect of the countermeasures to control rapid test ordering using a test utilization dashboard. Methods: Interventions were made to preserve a severely limited supply of rapid diagnostic tests based on real-time analysis of a COVID-19 test utilization dashboard. This study is a retrospective observational study evaluating pre- and postintervention rates of appropriate rapid test use, reporting times, and cost/savings of resources used. Results: This study included 14, 462 severe acute respiratory syndrome coronavirus 2 reverse transcriptase polymerase chain reaction tests ordered during the study period. After the intervention, there was a 27.3% decrease in nonconforming rapid tests. Rapid test reporting time from laboratory receipt decreased by 1.47 hours. The number of days of rapid test inventory on hand increased by 39 days. Conclusions: Performing diagnostic test stewardship, informed by real-time review of a test utilization dashboard, was associated with significantly improved appropriate utilization of rapid diagnostic COVID-19 tests, improved reporting times, implied cost savings, and improved reagent inventory on hand, which facilitated the management of scarce resources during a pandemic.